2018
DOI: 10.1016/j.hpb.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of complications after laparoscopic cholecystectomy: a systematic review

Abstract: Considerable variation was identified between studies in the choice of measures used to evaluate the complications of LC, and in their definitions. A standardised set of core outcomes of LC should be developed for use in clinical trials and in evaluating the performance of surgical units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 64 publications
(45 reference statements)
0
61
1
6
Order By: Relevance
“…Higher rate for surgical intervention was due to the delayed referral and the occurrence of enteric injuries as well. Delayed referral to a specialized center has been associated with increases the morbidity 17. We did not observe higher mortality due to delayed referral.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Higher rate for surgical intervention was due to the delayed referral and the occurrence of enteric injuries as well. Delayed referral to a specialized center has been associated with increases the morbidity 17. We did not observe higher mortality due to delayed referral.…”
Section: Discussioncontrasting
confidence: 52%
“…The exact incidence of enteric injury during cholecystectomy is unknown as it is being reported rarely. In a recent review reporting of complications after laparoscopic cholecystectomy, the entire emphasis was laid on bile duct injuries 17. There is not even a single large series which has reported any enteric injury 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although laparoscopic cholecystectomy has a low surgical risk and is the most common elective abdominal surgery performed in the US 174 , a series of complications is possible, ranging from conversion to open cholecystectomy (the most frequent) to bile leak, bile duct injury, and (in few cases) death 175 . It was recently suggested that surgical complications are more likely in patients with low socioeconomic status, who appear to be more vulnerable.…”
Section: Future Perspectives: From Therapy To Preventionmentioning
confidence: 99%
“…Nowadays, preservation of cholecyst has been increasingly getting attention with awareness of the various complications of cholecystectomy and the significance of gallbladder function. [ 3 5 ] With the development of endoscopic ultrasound (EUS)-guided transmural cholecystostomy using lumen-apposing metal stent (LAMS), per-oral transmural endoscopic resection of gallbladder polyps was introduced. [ 6 ] Through this pathway, endoscopic resection of gallbladder polyps with gallbladder preservation becomes possible.…”
Section: Introductionmentioning
confidence: 99%